Penerapan Kombinasi Metode MOORA dengan Pembobotan Rank Order Centroid Dalam Penentuan Guru Terbaik - Lusiyanti Lusiyanti; Feri Setiawan; Puji Sari Ramadhan (STMIK Budi Darma, 2022)
In this study, the authors conducted research on the topic of decision support systems in determining the best teacher. The case study used is at SMK Negeri 1 Lima Puluh Batubara Regency, North Sumatra Province. In practice, the selection of the best teachers and achievers in these schools has not been carried out objectively or in other words, the selection of the best teachers is still carried out in a subjective way where the validation in its determination is not known for certain openness. So to overcome this problem, the authors propose to apply the calculation of the Decision Support System (DSS) in solving these problems. The method used in this study is the MOORA method and uses the criteria weighting method with Rank Order Centroid. The criteria used are five criteria consisting of Teaching Method (K1), Motivation and Innovation (K2), Responsibility (K3), Problem Solving (K4), and Insight and Creativity (K5). Then the alternative data samples used were as many as ten data from SMK Negeri 1 Lima Puluh. The test results obtained were Iswanto (A3) obtained the highest final preference value of 0.4182 and could be declared the best teacher with the first rank. Then it can be seen that the MOORA and Rank Order Centroid methods are able to provide recommendations for the best teacher decisions at SMK Negeri 1 Lima Puluh using objective calculations.